Cartographer's experience of time in the Mercator-Hondius Atlas (1606, 1613) - Tunturi. Janne (The Donner Institute, 2022)
This article analyses the articulations of temporality in the Mercator-Hondius Atlas. Firstly, the atlas reflects the sense of the past as the cartographers had to assess the information included in ancient texts in relation to modern testimonies. Secondly, Hondius had to take into account the worldview provided-by the explorers in the fifteenth and sixteenth centuries. Hence the experience of time articulated in the Mercator-Hondius Atlas reflected not only the cartographers' ideas of the Dutch cartographic industry but also directed the making of the atlas.